TIPE KOMUNITAS HUTAN LAHAN KERING DI HUTAN LINDUNG SENTAJO, KABUPATEN KUANTAN SINGINGI, RIAU Community Types of Dryland Forest Within The Sentajo Protected Forest, Kuantan Singingi Regency, Riau Province - Pebriandi .; Omo Rusdiana; Muhammad Buce Saleh (Jurnal Silvikultur Tropika, 2017)
Sentajo Protected Forest located in Kuantan Singingi Regency, Riau Province. There is no information about vegetation diversity in this location. Therefore this study was conducted. This study aimed to determine the diversity of vegetation, structure, and composition of each community in Sentajo Protected Forest. The study was conducted in April-September 2016. A sampling design was determined using systematic sampling with random start. The sampling intensity used was 5%. The parameters measured in this study were the importance value index, similarity index between communities, species diversity index, evenness index, dominance index, regeneration, as well as horizontal and vertical structures. Based on the type of soil, elevation, and slope, 6 communities were grouped from the dense coverage area (forested). The results showed that the Sentajo Protected Forest had 424 flora consisted of 254 species, and 102 families. Sentajo Protected Forest had similarity index between 18 - 64%, species diversity index of 2.62 - 4.15, evenness index of 0.59 - 0.86, dominance index of 0.02 - 0.08. The larger the diameter of the tree, the smaller the number of individuals. The stratification of the canopy had 5 layers of canopy. Sentajo Protected Forest regeneration was relatively good as the number of seedlings> saplings> mature trees.Key words: community, composition and structure, diversity, Sentajo Protected Forest.